The effect of kneading technique on reducing the level of pain in the first stage of labor in mothers giving birth at the borong complex health center, sinjai regency in 2023 - Jusmawati, Jusmawati; Hasrida, Hasrida (CV. Paperhome Indonesia, 2024)
Background: Labor pain is an unpleasant sensation that occurs during the birth process. Physiologically, labor pain begins to appear in the latent phase of the first stage of labor and the active phase of labor. In the active phase, the size of the opening ranges from 4 to 10 cm. Uterine contractions and cervical dilation cause pain. Handling labor pain with non-pharmacological techniques such as squeezing is very important. The purpose of this study was to determine the effect of squeezing techniques on the level of labor pain in the first stage of labor in mothers giving birth at the Borong Complex Health Center. Method: This type of research is a quantitative experiment with a one-group pre-test and post-test design. This study involves 15 people. The purposive sampling method was used. The SPSS program was used to process univariate and bivariate data. Results: The Wilcoxon Signed Rank Test yielded a p-value of 0.000, thus α = 0.05. There is a significant effect on the level of pain in first-stage laboring mothers before and after the kneading technique. The average pain level of laboring mothers during the first stage before the kneading technique was 3.21 with a standard deviation of 0.378. The average pain level of laboring mothers during the first stage after the kneading technique was 2.15 with a standard deviation of 0.516, and the p-value was 0.000. Conclusion: The results of this study indicate that there is a relationship between the kneading technique and the level of labor pain during the first stage. It is hoped that the findings of this study can improve the quality of ideal intranatal midwifery services and serve as a new method to help pregnant women cope with labor pain.